1996
DOI: 10.1046/j.1365-2265.1996.631456.x
|View full text |Cite
|
Sign up to set email alerts
|

A case of silent 21‐hydroxylase deficiency with persistent adrenal insufficiency after removal of an adrenal incidentaloma

Abstract: A case of an adrenal incidentaloma in a 57-year-old man with silent 21-hydroxylase deficiency is reported. Abdominal computed tomography revealed a right adrenal tumour of 6cm in diameter. There was no evidence of adrenal hormone excess. However, after surgical removal of the adrenal tumour, the patient developed acute adrenal insufficiency. Adrenocortical function has remained low ever since surgery. Pathological examination of the tumour revealed a cortical adenoma. On the basis of increased plasma renin act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 18 publications
2
15
1
Order By: Relevance
“…In contrast, others have only found 0.5 % of the patients with adrenal incidentalomas to be affected by CAH [183], and some have reported that their finding of 9.6 % CYP21A2 carriers with nonfunctioning adrenal incidentaloma was not different from that in healthy controls [184]. How frequently an adrenal incidentaloma presents symptoms of NCAH is unclear, but there are several reports of NCAH diagnoses as the result of the work-up of these tumors [24,29,[180][181][182]185]. In some of these cases, the diagnosis of CAH, both classic and NCAH, was made on the urinary steroid profile sampled in the work-up of suspected adrenocortical cancer [24,29,185].…”
Section: Adrenal Tumorsmentioning
confidence: 89%
“…In contrast, others have only found 0.5 % of the patients with adrenal incidentalomas to be affected by CAH [183], and some have reported that their finding of 9.6 % CYP21A2 carriers with nonfunctioning adrenal incidentaloma was not different from that in healthy controls [184]. How frequently an adrenal incidentaloma presents symptoms of NCAH is unclear, but there are several reports of NCAH diagnoses as the result of the work-up of these tumors [24,29,[180][181][182]185]. In some of these cases, the diagnosis of CAH, both classic and NCAH, was made on the urinary steroid profile sampled in the work-up of suspected adrenocortical cancer [24,29,185].…”
Section: Adrenal Tumorsmentioning
confidence: 89%
“…The production of cortisol by the tumor is supported by the finding that the ectopic but discernible expression of CYP21 in the tumor. To the best of our knowledge, there is one report that suggests the production of cortisol by the adrenal tumor arising in the patient with 21OHD (Nagasaka et al 1996). They reported that adrenal insufficiency developed after the surgical removal of the adrenal tumor and the pathological diagnosis was adrenocortical adenoma.…”
Section: Discussionmentioning
confidence: 99%
“…Following discovery of an adrenal incidentaloma, an 88 year old women was diagnosed with NCAH; her genetic analysis showed V281L and I172N [70]. A 57 year old man ascertained by finding an adrenal incidentaloma was diagnosed with NCAH; he had elevated serum 17-OHP concentrations and urinary 17-ketosteroid excretion [71]. Adrenal myelolipomas have been reported among untreated adults with NCAH [72].…”
Section: Other Considerationsmentioning
confidence: 99%